KAJIAN INTERPRESTASI UNSUR ALAM DALAM SEMPAMA JAKU IBAN: ANALISIS IMPLIKATUR - Jenny Janie, Tujang (Universiti Malaysia Sarawak (UNIMAS), 2025)
This study explores the interpretation of natural elements in Sempama Jaku Iban (Iban proverbs) using implicature analysis based on the Relevance Theory proposed by Sperber and Wilson (1986). Sempama, as a form of oral literature within the Iban community, is rich with natural symbolism that reflects life philosophy, social norms, and moral values. This qualitative research analysed 20 selected nature-based proverbs sourced from the book Sempama Jaku Iban (Iban Metaphor) by Casper Kayong Umping (2010). The data were analysed by mapping explicit and implicit meanings to uncover both literal and underlying messages conveyed through elements such as flora and fauna. Findings reveal that natural elements are widely used as metaphors to deliver moral advice, social criticism, and cultural values that are deeply connected to the Iban way of life. This study also proposes several strategies to sustain the use of Sempama Jaku Iban in modern educational and cultural contexts. Ultimately, the study contributes not only to a deeper pragmatic understanding of Iban proverbs but also supports the preservation of the Iban community’s linguistic and cultural heritage.